THE DEVELOPMENT OF STUDENT WORKSHEET BASED ON HIGHER ORDER THINKING SKILLS IN IMPROVING MATHEMATICS LEARNING OUTCOMES - Kuswari, Retno Intan; Choiruddin, Choiruddin (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
The use of instruction tools that only explains the instruction material, but does not know the extent to which students' understanding causes the instruction process to be less than optimal. This study aims to find out the development process, feasibility, and the influence of using student worksheet based on higher order thinking skills in improving Mathematics learning outcomes at MIN 3 Tulungagung and SDI Qurrota A'yun Ngunut Tulungagung. This study uses the development research model of Borg, and Gall. The results show that: (1) The development of HOTS-based worksheets begins with preparing instruction materials in accordance with the Core Competencies and Basic Competencies listed in the 2013 Curriculum.Furthermore, the researcher makes examples of HOTS questions that are in accordance with the material that has been presented, making questions individual and group practice questions and then make competency test questions at the end of the chapter. (2) The worksheets based on HOTS are suitable for use in improving Mathematics learning outcomes. This can be seen from the results of due diligence by media and material experts. (3) There is an influence of using HOTS-based worksheets as indicated by the significant difference in learning outcomes between the experimental class that does instruction using HOTS-based worksheets and the control class that does instruction without HOTS-based worksheets. This is based on the data from the t-test results in which sig-2 0.040 <0.050 is obtained.